2022
DOI: 10.3389/fgene.2022.964684
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing genomics and historical data to optimize gene pools for new breeding programs: A case study in winter wheat

Abstract: With the rapid generation and preservation of both genomic and phenotypic information for many genotypes within crops and across locations, emerging breeding programs have a valuable opportunity to leverage these resources to 1) establish the most appropriate genetic foundation at program inception and 2) implement robust genomic prediction platforms that can effectively select future breeding lines. Integrating genomics-enabled1 breeding into cultivar development can save costs and allow resources to be reall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…The AVG method only in few cases was better than the conventional method, while in the CD and PEV we observed that these methods in any case were superior in terms of prediction accuracy than the conventional method; this lack of efficiency of the CD and PEV methods was also reported by Berro et al (2019) for optimization strategies to choose individuals from the training population with higher predictive ability for a specific testing set. Also, regarding the CD method, Ola- and PEV methods when the testing set is not defined a priori and after selecting the optimal training the remaining individuals constitutes the testing set (Ballén-Taborda et al, 2022;Rincent et al, 2017Rincent et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVG method only in few cases was better than the conventional method, while in the CD and PEV we observed that these methods in any case were superior in terms of prediction accuracy than the conventional method; this lack of efficiency of the CD and PEV methods was also reported by Berro et al (2019) for optimization strategies to choose individuals from the training population with higher predictive ability for a specific testing set. Also, regarding the CD method, Ola- and PEV methods when the testing set is not defined a priori and after selecting the optimal training the remaining individuals constitutes the testing set (Ballén-Taborda et al, 2022;Rincent et al, 2017Rincent et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they strongly advise against employing the CD procedure in practical applications and instead propose utilizing all available individuals as the training set. However, some other studies have shown a gain in prediction accuracy by implementing CD and PEV methods when the testing set is not defined a priori and after selecting the optimal training the remaining individuals constitutes the testing set (Ballén‐Taborda et al, 2022; Rincent et al, 2017, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Historical data for FHB partial-resistance QTL were used to assess potential yield drag for several moderate effect QTL across three major southern SRWW production environments (Ballén-Taborda et al, 2022). The three resistance QTL selected were Qfhb.…”
Section: Impact Of Molecular Breeding To Accelerate Improvement Of Fh...mentioning
confidence: 99%
“…A multi‐environment study across the southeastern United States used a QTL‐by‐environment approach to correlate yield with various resistance genes across three major wheat‐growing regions. H13 , which is used widely in this region, was in ∼11% of the 1104 breeding lines in the study and had a positive effect on grain yield (Ballen et al., 2022). This collaborative breeding group successfully used genomic prediction for multiple traits, including Hessian fly resistance, on a large group of wheat genotypes and breeding lines (Ballen et al., 2022).…”
Section: Genome‐wide Association Mapping and Genomic Predictionmentioning
confidence: 99%
“…H13 , which is used widely in this region, was in ∼11% of the 1104 breeding lines in the study and had a positive effect on grain yield (Ballen et al., 2022). This collaborative breeding group successfully used genomic prediction for multiple traits, including Hessian fly resistance, on a large group of wheat genotypes and breeding lines (Ballen et al., 2022).…”
Section: Genome‐wide Association Mapping and Genomic Predictionmentioning
confidence: 99%